PENGARUH PERTUMBUHAN EKONOMI, INFLASI, PENDIDIKAN DAN RASIO GINI TERHADAP PENGANGGURAN TERBUKA DI KOTA SIBOLGA PERIODE 2002-2021 - Ramadhan Devan Pratama (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Open unemployment is a condition where the workforce already has the skills but does not yet have a job. The problem of open unemployment is a complicated problem to be avoided by a country or region. If the open unemployment rate in an area tends to be high, it will slow down the achievement of the economic development targets that have been set. In addition, it will trigger other social issues such as increasing crime rates and economic issues such as decreasing people's purchasing power which will result in a decrease in demand for the results needed for production goods in a region. This research intends to find out the effect of Economic Growth, Inflation, Education and Gini Ratio on Open Unemployment in Sibolga City for the period 2002-2021. The media analysis in this research uses multiple linear regression analysis which is analyzed with the help of software, namely SPSS 19. The results of the research confirm that there is a significant negative influence of economic growth and education level on open unemployment. On the other hand, there is a positive influence from the independent variables, namely inflation and the Gini ratio on open unemployment although it is not significant. Based on the results of this research, it is appropriate for the Sibolga City Government to optimize programs that are oriented towards increasing economic growth, suppressing inflation rates, advancing the quality of education and decreasing the Gini ratio simultaneously in the Sibolga city area.